Equality as a threshold conception: challenging future manager's perceptions. Issue 7 (18th September 2018) - Dyer, Suzette; Hurd, Fiona
Abstract : Purpose: The purpose of this paper is to examine the potential to develop a shared understanding of systemic discrimination and the complexity of equality and an appreciation for the range of interventions designed to redress inequality within the context of business school curricula. Design/methodology/approach: Qualitative material was gathered over a four-year period through written reflections of student interpretations of equality. Participants were enroled in a human resource management (HRM) course critically examining systemic gender discrimination, women's organisational experiences, gendered employment outcomes and the range of interventions designed to redress gendered employment outcomes. Threshold concepts framed the analysis of participant reflections. Findings: The paper shows that while the participants developed a shared understanding of systemic gender discrimination, their interpretations of equality and appreciation for the range of interventions available to redress inequality differed. These differences were shaped by the extent to which participants integrated their understanding of systemic discrimination with their interpretations of equality, and the extent to which the interventions to inequality transformed, upheld or challenged participant agendic self-identity and world view. Research limitations/implications: The study provides support for continued use of equality as a construct in both research and teaching settings. The study highlights that unequal outcomes are an enduring phenomena, and that introducing the notion of equality to the classroom helps develop student's ability to understand dynamics of discrimination in the workplace. The limitations of the study relate to the sample size, and dependence on a single specialist HRM course, in addition to the specific New Zealand context. Practical implications: The differences in interpretations have implications for the way educators introduce discussions of equality within the business school classroom. Originality/value: The paper demonstrates that developing a shared understanding of systemic discrimination does not always lead to developing a shared understanding of the complexity of equality or appreciation for the many forms of interventions available.